Study of Antioxidant Activity of Rice and Oat bran protein Isolates - صلبوخ منال عبد الواحد (Journal of Kerbala for Agricultural Sciences, 2016)
The present study aimed to prepare a protein isolates from the local defatted oat and rice bran to study their chemical composition and biological activity as anti-oxidant in vitro . The percent of protein in rice bran and isolate was reached (10.87 - 91.27) % and about( 12.10 - 88.87) % for oat bran and isolate .The protein isolates showed antioxidant function as measured by the DPPH radical-scavenging and the recorded values were (68,58)% for oat and rice isolate respectively. Metal chelating activity test showed higher values being (72,69) % respectively and the reducing power activity test gave (69,84)% .This research is a considered as applicable research because it used the by products to prepare a valuable product can used it as food fortification and protein sources .